(6x+10)+(13x+5)=

Simple and best practice solution for (6x+10)+(13x+5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x+10)+(13x+5)= equation:


Simplifying
(6x + 10) + (13x + 5) = 0

Reorder the terms:
(10 + 6x) + (13x + 5) = 0

Remove parenthesis around (10 + 6x)
10 + 6x + (13x + 5) = 0

Reorder the terms:
10 + 6x + (5 + 13x) = 0

Remove parenthesis around (5 + 13x)
10 + 6x + 5 + 13x = 0

Reorder the terms:
10 + 5 + 6x + 13x = 0

Combine like terms: 10 + 5 = 15
15 + 6x + 13x = 0

Combine like terms: 6x + 13x = 19x
15 + 19x = 0

Solving
15 + 19x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + 19x = 0 + -15

Combine like terms: 15 + -15 = 0
0 + 19x = 0 + -15
19x = 0 + -15

Combine like terms: 0 + -15 = -15
19x = -15

Divide each side by '19'.
x = -0.7894736842

Simplifying
x = -0.7894736842

See similar equations:

| (5x+4)+(2c+8)= | | 26=6+5(x+1) | | 3x^3-(24/27)y^6=0 | | 7n-6n=20 | | 5x+6x+12-10=90 | | 6(3a+5b)= | | 16-13=2x-7 | | 4=13x+40 | | X/-4-6=3 | | Y=14-2xslope | | 8x-1/3x=0 | | 2(x+5)=14x-8 | | -4c*-4c+8c*8c= | | 7-2(6n+8)= | | p+76=49 | | -6(-3+x)=30 | | -8x+2y=-4 | | 2x+29=7+x+12 | | 4x+5x-2=o | | f=-1+-27x | | -4.8j+6.4=-8.48 | | 1/3.6=7.28 | | 19+x=180 | | 9p^2+6p+4=0 | | y-1=-2/9(18) | | 2=28-4x | | (4-(1/t))-(3/t^2)=0 | | 12p+3p=-20+2p+3p | | H+8=7 | | 2/n=9/2 | | B+20=40 | | -19x^2+8x=0 |

Equations solver categories